PSVIII-25 Expression and Secretion of circulating galectins in domestic ruminants. (7th December 2018) - Worku, M; Ekwemalor, K; Asiamah, E; Adjei-Fremah, S; Osei, B; Mulakala, B; Eluka-Okoludoh, E; Ismail, H
Abstract: The objective of this study was to compare galectin gene (LGALS) expression and secretion in cow, sheep and goat blood. Ruminants succumb to infectious and metabolic diseases. Galectins (Gals) are a family of β –galactoside binding proteins that have a conserved carbohydrate recognition domain increasingly recognized for their role in inflammation. At least 15 Gals are secreted intracellularly and extracellularly. They are involved in cell adhesion, migration, activation, proliferation, apoptosis and modulate pathological processes such as inflammation. Little is currently known about the expression and physiological role of circulating galectins in animals. A comparative study was done to determine the expression and secretion of galectins in blood from adult non-pregnant female sheep, cows and goats (N=3 each). Total RNA was isolated using Tri-reagent (Sigma) and reverse-transcribed to cDNA. Commercially sequenced species specific primers for Galectins were used for real-time PCR. GAPDH and beta-actin served as internal controls. Enzyme-linked Immunosorbent assay was used to detect and determine the concentration of structurally different Galectins, Gal 1(Prototype), Gal 3 (chimera type) and Gal 9 (tandem-repeat type) in plasma. Galectin secretion was analyzed with Proc GLM in SAS 9.4. All Galectins tested (1, 2, 3, 4, 7, 8, 9, 11 and 12) were expressed in cows, goats and sheep blood. Galectins 1, 3 and 9 were secreted in plasma at varying concentrations ranging from pg/mL to ng/mL. The hierarchy was Gal1>Gal 3>Gal 9. Diversity was observed in level of expression and secretion among the three species. Extracellular secretion of Gal was related to structure. This may have implications for Gal function and possible use as preventives diagnostic and therapeutic in ruminants. Studies are underway to further analyze the role of circulating Gal in homeostasis and health.